ANALISIS VIDEO PEMBELAJARAN MATEMATIKA MAHASISWA PGSD UNIVERSITAS MATARAM PADA MATA KULIAH PEMBELAJARAN MATEMATIKA SD - Radiusman, Radiusman; Simanjuntak, Maslina (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This qualitative research aims to analyze the stages of mathematics learning activities carried out by primary school teacher candidates at the University of Mataram. The data analysis of this research was conducted in a descriptive qualitative manner. The research subjects were randomly selected consisting of two primary school teacher candidates who have different genders but have the same academic ability. The data analysis process was carried out by collecting data, presenting data, and drawing conclusions. Data collection was obtained through instructional videos of primary school teacher candidates in primary school mathematics learning courses . The presentation of data is done by describing the stages of learning activities that the teacher must do in the classroom. The results of this study indicate that the research subjects have their respective strengths and weaknesses in the implementation of learning activities, the material abilities of the research subjects are still weak in learning activities and the research subjects do not utilize/use knowledge in previous courses to improve teaching quality.